Soil quality and its determinants in saline-alkali land of northwest China - Wei, Wei; Xiao, Qinghong; Bai, Yan; Wang, Wei; Wang, Huibin; Yang, Wenna; Liu, Yanru; Wu, Kunyue; Wu, Dongbo; Zhao, Yan; Gong, Xue (Frontiers in Environmental Science, 2025)
BackgroundIn response to the need for saline-alkali land management in the Ningxia section of the Yellow River Basin, current research is often limited to single indicators or small-scale analyses, lacking a systematic assessment of multi-factor interactions and macro-scale spatial heterogeneity.MethodsThis study selected 13 typical districts and counties in Ningxia. Based on topography, land use, and salinization degree, a stratified random sampling design was employed, resulting in 2,543 sampling points. Multi-source data were integrated, encompassing four main categories: soil (physicochemical properties), topography (area, textural configuration), management (drainage capacity, shelterbelt network, cultivation system), and biology (plant and microbial biodiversity). The Analytic Hierarchy Process (AHP) was used to determine indicator weights. The spatial variation of soil quality was assessed by calculating the Integrated Fertility Index (IFI). Path analysis and JMP power analysis were utilized to quantify the direct, indirect, and interactive contributions of various influencing factors.ResultsSoil salinity and nutrients exhibited a spatial pattern of “higher in the north and lower in the south” with soil quality grades decreasing from north to south. Path analysis identified soil pH, alkali-hydrolyzed nitrogen (AHN), topsoil texture, and drainage capacity as the core factors affecting soil quality. Among these, topsoil texture had the highest contribution (20.47%), and the interaction between pH and AHN was the most significant (4.84%). Areas with high biodiversity highly aligned with regions of low salinity and high organic matter content.ConclusionThe quality of saline-alkali land is co-regulated by natural factors and human management measures, with topsoil texture and drainage capacity being the key controlling elements. These findings provide a theoretical basis and technical support for the “zoned management and functional coordination” of saline-alkali land in the irrigation areas of Northwestern China.